The role of regulation in medical student learning in small groups: Regulating oneself and others' learning and emotions. (November 2015) - Lajoie, Susanne P.; Lee, Lila; Poitras, Eric; Bassiri, Mandana; Kazemitabar, Maedeh; Cruz-Panesso, Ilian; Hmelo-Silver, Cindy; Wiseman, Jeffrey; Chan, Lap Ki; Lu, Jingyan
Highlights: Computer supported collaborative problem based learning in medicine can lead to high levels of metacognition. High co-regulation in problem based learning co-occurs with levels of Interactive Social Presence. Co-regulatory actions that activate the discussion and metacognitive acts of planning. Abstract: This study examines the role of regulatory processes in medical students as they learn to deliver bad news to patients in the context of an international web-based problem based learning environment (PBL). In the PBL a medical facilitator and students work together to examine video cases on giving bad news and share their perspectives on what was done effectively and what could be done differently. We examine how regulation occurs within this collaboration. A synchronous computer-supported collaborative learning environment (CSCL) facilitated peer discussion at a distance using a combination of tools that included video-conferencing, chat boxes, and a shared whiteboard to support collaborative engagement. We examine regulation along a continuum, spanning from self- to co-regulation, in situations where medical students learn how to manage their own emotions and adapt their responses to patient reactions. We examine the nature of the discourse between medical students and facilitators to illustrate the conditions in which metacognitive, co-regulation and social emotional activities occur to enhance learning about how to communicate bad news to patients.